Experimental Analysis of the Characteristic of the Plasma Welded Components - Mohd Akhmal Bin Ab Kadir @ Abd Kadir (School of Materials Engineering, University Malaysia Perlis, 2009)
The main aim of this project is to study plasma arc cutting when using it for welding process. Basically, plasma arc cutting just used for cutting process, but actually it also can perform for welding process. So, this study is to determine the best combination of parameter in plasma arc cutting to perform the welding process. For overall, it is about experimental analysis of the characteristics of the plasma welded components. For this project, plasma arc cutting will be utilized and it just focuses in welding process. In this project several experiments will be conducted to determine the efficiency with different operating parameter. Design of experiment (DOE) will be utilized to study factors behaviour over performance measures. The DOE approach is proved to be highly effective for measuring performance of a process which is controlled by more than one factor such as air pressure, current flow rate, welding speed and welding angle in plasma arc cutting. The output or responses for this experiment are strength of joint the material that welded.